Public Relations Strategy Based on Social Media Engagement to Strengthen the Image of Islamic Educational Institutions - Ahmad Rausyan Fikri; Moh Mohlas; Annisa Tri Ananda Dewi; Muthi’ah Rahman; Maulidatul Adzimah; Abdul Aziz Alwahedi; Moh Jasri (Education and Sociedad Journal, 2025)
This study aims to analyze Public Relations strategies based on social media engagement in strengthening the image of Islamic educational institutions, identify models that integrate turats values into digital communication practices, and examine the contribution of audience engagement to institutional image formation. This research uses a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving social media managers, institutional leaders, lecturers, students, and digital content produced by the institution. Data analysis followed data reduction, data presentation, and thematic conclusion drawing techniques. The findings indicate that the Public Relations strategy is built through the integration of turats values with relevant digital content, the implementation of social media engagement that fosters active interaction between the institution and its audience, and the development of a hybrid PR model combining traditional pesantren communication with modern digital communication. The results also show that religious engagement is a key factor in strengthening trust, legitimacy, and a positive institutional image in digital spaces. The study implies that strengthening the image of Islamic educational institutions requires adaptive, participatory, and value-based communication strategies grounded in Islamic principles to enhance institutional reputation and sustainability in the digital era.